Developing cetacean-friendly guidelines, from whale watching to offshore wind farm operation - Chen, Yu-Ju; Lee, Pey-Yi (Frontiers in Marine Science, 2023)
Developing offshore wind farms may impact cetaceans due to vessel collisions and underwater noise. Therefore, it is critical to protect cetaceans while developing offshore wind farms. We first studied the code of conduct/guidelines for whale watching and then interviewed members of the local whale-watching industry to learn about the interaction between cetaceans and vessels. After that, we compared current whale-watching guidelines in Taiwan with 69 published guidelines from other countries and locations, then developed guidelines for the offshore wind farm industry. The results show that rules related to approaching and interacting with cetaceans in Taiwan are similar to those in other countries. However, swimming with cetaceans and approaching calves are prohibited in Taiwan. From the survey of the whale-watching industry, most whale-watching guidelines in Taiwan were found to be feasible, and the guidelines should be described in the premise with different phenotypic traits of various cetaceans. Based on the whale-watching guidelines, we developed a code of conduct for protecting cetaceans from the impact of vessels, specifically in offshore wind farm operations in Taiwan.